Basic documents on human rights - "Brownlie, Ian ed." (Oxford, 1971)
This is the eagerly awaited new edition of the established text Basic Documents on Human Rights which is an essential resource for all undergraduate students. The book provides an extensive collection of key documents and covering all elements of the subject, e.g. the Declaration on the Elimination of Violence against Women, accompanied by authoritative commentary and annotation. The result is a clear and accurate account of the most important Human Rights instruments adopted by the United Nations and its agencies, by regional organisations and other actors in the field. Forty new or amended instruments are featured in this edition and coverage of the new treaties and conventions includes; the Declaration on the Rights of Persons Belonging to National or Ethnic, Religious, or Linguistic Minorities, new treaties in emerging areas such as bio-ethics and a variety of additional protocols including those on civil and political rights, women and children. A new section of the text identifies the current number of States parties and directs the reader to the internet and other sources providing access to the latest information on ratifications, reservations and declarations.
Keywords: Civil Rights